2004
DOI: 10.1677/joe.1.05549
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cAMP-dependent protein kinase (PKA) and progesterone secretion in luteinizing human granulosa cells

Abstract: Luteinization of follicular granulosa cells leads to an increase in progesterone secretion that is regulated by luteinizing hormone (LH). LH acts mainly by elevating intracellular cyclic 3 ,5 -adenosine monophosphate (cAMP) and activating cAMP-dependent protein kinase (PKA). In this study, we have examined the role of PKA in relation to progesterone output by luteinizing human granulosa cells. Human granulosa cells were obtained by percoll gradient centrifugation of follicular aspirates of patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…This increases intracellular cAMP, thereby activating protein kinase A and inducing expression of PR (29,30). Our in vivo study also indicates that the PKA protein is activated by hCG and that in vitro H89 reduces significantly PR expression.…”
Section: Discussionsupporting
confidence: 65%
“…This increases intracellular cAMP, thereby activating protein kinase A and inducing expression of PR (29,30). Our in vivo study also indicates that the PKA protein is activated by hCG and that in vitro H89 reduces significantly PR expression.…”
Section: Discussionsupporting
confidence: 65%
“…In preantral follicles PDE4D and PDE3A were expressed to a significantly higher extent than in the GCs of later follicle stages as indicated by microarray data. As shown previously (Chin et al, 2004), when GCs isolated after ovulation induction were cultured in the presence of forskolin the cells were stimulated via cAMP to produce progesterone. Inhibition of PDE4 (i.e., by roflumilast) further increased the forskolininduced progesterone production, while there was no effect on the non-forskolin stimulated GCs.…”
Section: Discussionmentioning
confidence: 56%
“…Since we have previously shown that gonadotrophins, as well as other agents that raise intracellular cAMP, were able to increase progesterone secretion during the luteinization of human granulosa cells (Chin et al 2004), we went on to investigate the effect of PKA inhibition on agonist-induced progesterone secretion. Granulosa cells were incubated on days 1 (0-24 h) and 3 (48-72 h) of culture in the presence of hLH (100 ng/ml), the adenylate cyclase activator forskolin (10 µM) or the cell-permeable cAMP analogue, dbcAMP (5000 µM), with or without increasing doses of the PKA inhibitor, H89 (0·1-10 µM).…”
Section: Effect Of Pka Inhibition By H89 On Hlh- Forskolin-and Dbcammentioning
confidence: 99%
“…We have previously shown that, during luteinization of human granulosa cells, gonadotrophin-induced progesterone secretion is coincident with a decrease in the expression of the active catalytic subunit of PKA (Chin et al 2004), a finding which suggests that, during luteinization, increases in progesterone secretion can be dissociated from increases in PKA expression/activity; that is, steroid synthesis becomes less dependent upon PKA as luteinization proceeds. Both cAMP-GEFs (I and II) and the effector Rap are expressed in granulosa cells at the level of mRNA (Gonzalez-Robayna et al 2000).…”
Section: Introductionmentioning
confidence: 98%